FEM Analysis and Experimental Study on the Bending Strength of Ceramic Tiles with the Top- and Back-Sided Polyurea Coating - Kamonchaivanich, K.; Kuboyama, K.; Ougizawa, T. (Проблемы прочности, 2018)
Mechanical properties enhancement of ceramic tiles by a simple coating technique using polyurea was investigated. Solventless polyurea coatings were employed. The effect of coating sides of the ceramic substrate and film thickness on the mechanical properties were examined in three-point bend tests. The back-coated ceramic tile demonstrated a significant improvement in bending strength (by 25–50%) as compared to the top-coated one. The stress distribution in the substrate was analyzed by the finite element method, and the mechanism of improving mechanical properties was discussed. Изучена возможность улучшения механических свойств керамической плитки путем нанесения покрытия из полимочевины. Использовано покрытие из полимочевины без растворителя. Влияние стороны нанесения покрытия на керамическую основу и толщины пленки на механические свойства исследовано при испытаниях на трехточечный изгиб. Прочность при изгибе керамической плитки с покрытием на нижней стороне существенно лучше (на 25...30%) по сравнению с таковой покрытия, нанесенного на ее лицевyю поверхность. Выполнен анализ распределения напряжений в основе с помощью метода конечных элементов и проведено обсуждение механизма улучшения механических свойств.